The impact of energy prices on electric vehicle adoption: From a perspective of consumer expectations - Xiaolei Zhao; Xuemei Li; Anqi Wang; Jianjun Fang (Sustainable Futures)
The rapid adoption of electric vehicles (EVs) is critical to achieving sustainable transportation, yet the role of energy prices in shaping consumer decisions remains underexplored, particularly in terms of their relative effects. This study provides a methodological and empirical contribution to understanding the role of energy prices in electric vehicle (EV) adoption, a critical factor in advancing sustainable transportation. It employs a discrete choice model integrated with a regression discontinuity design to analyse the differential impacts of gasoline and electricity prices on EV adoption across 50 Chinese cities from 2010 to 2020. Methodologically, this approach allows for precise estimation of the causal effects of energy prices while controlling for potential confounding factors. Empirically, the study quantifies the relative influence of gasoline prices, which are found to have a significantly larger impact—approximately 3.5 to 6 times greater than electricity prices—on consumer adoption behaviour. Furthermore, it introduces an innovative framework to address consumer misperceptions of future electricity costs, estimating that up to 37 % of optimal EV subsidies are allocated to correcting these misjudgements. These findings offer novel insights for shaping more effective and sustainable transportation policies, bridging the gap between economic theory and real-world consumer behaviour.